Multidisciplinary analysis of combined flow-like mass movements in a catchment of Southern Italy. Issue 1 (2nd January 2021) - Cascini, L.; Cuomo, S.; Di Mauro, A.; Di Natale, M.; Di Nocera, S.; Matano, F.
ABSTRACT: Rainfall can trigger flow-like mass movements characterised by different percentages of solid and water (debris flows, hyperconcentrated flows, and flash floods). They exhibit different magnitude (volume), run-out distance and consequence, due to both distinct triggering mechanisms and kinematic features. Indeed, discriminating among these phenomena for appropriate risk analysis and zoning is a relevant issue also considering that the volume of the flow may sudden increase along the propagation path. The paper deals with September 2010 combined types of flows occurred at Atrani village (Amalfi coast, southern Italy), and originated by heavy rainstorm in the catchment located upslope to the urban centre. The events were reconstructed by using multi-source information. Field surveys, geological analysis, elaboration of videos recorded during the events and numerical modelling were combined. A 40 minutes lasting water flood abruptly combined to a relatively small-sized high-discharge hyperconcentrated flow, with the consequence of an abnormal flow that invaded the narrow main street of the urban area in few minutes. The peak discharge at the catchment outlet was increased by erosion and/or other rainfall-induced slope instabilities occurred in the whole catchment. As main conclusion, the multidisciplinary analysis has resulted effective to enhance the understanding of the complex flow-like mass movements.